2016
DOI: 10.1155/2016/5356307
|View full text |Cite
|
Sign up to set email alerts
|

Association between Air Pollution and the Development of Rheumatic Disease: A Systematic Review

Abstract: Objective. Environmental risk factors, such as air pollution, have been studied in relation to the risk of development of rheumatic diseases. We performed a systematic literature review to summarize the existing knowledge. Methods. MEDLINE (1946 to September 2016) and EMBASE (1980 to 2016, week 37) databases were searched using MeSH terms and keywords to identify cohort, case-control, and case cross-over studies reporting risk estimates for the development of select rheumatic diseases in relation to exposure o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
1
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(35 citation statements)
references
References 26 publications
1
30
1
3
Order By: Relevance
“…It has been reported that the immunotoxicity of PM plays an important role in the innate immune system and in cellular or humoral immunity [ 21 ]. Ambient PM 2.5 -related skin damage might be caused by activating the innate immune system.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that the immunotoxicity of PM plays an important role in the innate immune system and in cellular or humoral immunity [ 21 ]. Ambient PM 2.5 -related skin damage might be caused by activating the innate immune system.…”
Section: Discussionmentioning
confidence: 99%
“…asthma, chronic bronchitis, rhinitis) [ 3 ]. Recent evidence supports associations with diabetes [ 21 ], rheumatic diseases [ 22 ], cognitive functioning [ 23 ] and neurodegenerative diseases [ 24 ]. Furthermore, gases such as the secondary pollutant ozone are related to all-cause, circulatory and respiratory mortalities [ 3 , 25 ] as well as chronic respiratory diseases such as asthma [ 3 ].…”
Section: Interactions Between Climate Air Pollution and Healthmentioning
confidence: 97%
“…Air pollutants are part of the environmental components resulting from dust storms and fossil fuel combustion, which determine RA symptoms and worsen the overall disease. Additionally, gases such as SO 2 , NO 2 , carbon monoxide (CO), and O 3 are the other main pollutants that cause RA [8]. More in general, extensive investigations have been performed by several researchers about the impact of ambient air pollution on human health [9,10].…”
Section: Introductionmentioning
confidence: 99%